What did Jesus mean? explaining the Sermon on the Mount and the parables in simple and universal human concepts - Wierzbicka, Anna.; Oxford eBooks (Oxford : Oxford University Press, 2001)
Linguist Anna Wierzbicka casts new light on the words of Jesus by taking her theory of universal human concepts and bringing it to bear on Jesus' parables and the Sermon on the Mount. Her approach results in strikingly novel interpretations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Parables; Bible. -- Language, style; Electronic books